Effectiveness of the Use of Farmer Cards on the Distribution of Subsidized Fertilizer in Taliwang District, West Sumbawa Regency - Herlina, Herlina; Zulkieflimansyah, Zulkieflimansyah; Yamin, Ahmad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The government has a policy to provide fertilizer to farmers through fertilizer subsidies. However, in its implementation, there are obstacles such as supervision, procurement and distribution of fertilizers that are not on target, shortages, misuse and price increases for farmers. The government's effort to overcome this problem is by issuing the Tani Card program. This research discusses the effectiveness of the use of farmer cards in the distribution of subsidized fertilizer in Taliwang District, West Sumbawa Regency. The objectives of this research consist of; (1) to determine the effectiveness of the use of farmer cards in Kec. Taliwang, West Sumbawa Regency, (2) to determine the effectiveness of subsidized fertilizer distribution in the district. Taliwang, West Sumbawa Regency, and (3) to determine the influence of the use of farmer cards on the distribution of subsidized fertilizer in the district. Taliwang, West Sumbawa Regency. The type of research used in this research is quantitative descriptive. The population in this research is all farmers receiving subsidized fertilizer allocations in Taliwang District who are officially registered in the Taliwang District e-RDKK in 2024, a total of 4,142 farmers. Sampling in this research was carried out using the Slovin Method, so the number of samples obtained was 97.64 samples and rounded up to 100 samples. Data collection methods applied in this research include: Observation, interviews, questionnaires and documentation. Data were analyzed using the Guttman Scale. Based on the research results, it can be seen that the overall effectiveness of using the Farmer's Card is categorized as quite effective because it has a percentage of 78% yes answers and 22% no answers. Apart from that, overall, the distribution of subsidized fertilizer is categorized as quite effective because it has a percentage of 67% answers yes and 33% answers no. The results of the Spearman Rank Correlation Test show that there is a significant relationship between the effectiveness of the use of farmer cards (EPKT) and the distribution of subsidized fertilizer (PPS). The correlation coefficient value of 0.342 indicates that there is a weak relationship between the variable effectiveness of the use of farmer cards and the distribution of subsidized fertilizer. So it can be concluded that the Effectiveness of the Use of Farmer Cards on the Distribution of Subsidized Fertilizer in Taliwang District, West Sumbawa Regency, has a significant influence.